Seeking arm’s length: An evaluation of formulary apportionment and predetermined margins as alternative or supplementary methods to establish proxy arm’s length transfer prices for multinational intercompany transactions in South Africa - Raymond, Bonita (Department of Finance and Tax, 2020)
Since the inception of democracy in South Africa and the subsequent lifting of sanctions and trade embargos placed upon South Africa, the country’s economy has evolved from a much protected, inward looking economy into an internationally robust and competitive environment. Multinational enterprises (MNE’s) which seek to invest in a geographical region often choose certain countries as a base from which they can expand their investments to the other countries in the region. With its sizable economy, political stability relative to the rest of Africa and overall strength in financial services, South Africa should be the ideal location from which foreign investors can extend their investments into the rest of Africa (Ogutta, 2011). However, in South Africa foreign investment has reduced to an extent where local companies are now more invested in international markets than international investment in South Africa (Development, 2018). In monetary terms, at the end of 2017, South Africa had invested R3.3 trillion in foreign markets while foreign markets had only invested R 1.8 trillion in South Africa (Development, 2018). With the current global economic challenges, developing countries like South Africa have become increasingly aware of the importance of tax revenue and the effects of base erosion and profit shifting on the financial well-being of the state (OECD:G20 Working group, 2014); (Economic Commissions for Africa, 2018). Section 31 of the South African Income Tax Act, is the main section in the Act relating to transfer pricing in South Africa. Transfer pricing is one of the most important issues in international tax. It is estimated that more than 60% of international trade happens across borders but within the same corporate groups (Cobnam & Mcnair, n.d.). The transfer pricing rules of South Africa are closely aligned with the wording of the Organisation for Economic Cooperation and Development (OECD) and the United Nations (UN) Model Tax conventions and are in line with tax treaties and other international tax principals (SARS, 2010). The cornerstone of the transfer pricing model is the use of the arm’s length price. In terms of the arm’s length principle, in order to test the reasonability of pricing within MNE’s, tax authorities should use a similar but unrelated open market transaction as the benchmark to determine if there were any profit shifting to avoid tax by the MNE’s between their different establishments in the different tax jurisdictions. The biggest challenge in South Africa and other countries, when applying the arm’s length principle is the lack of local comparable data available to evaluate the transfer prices (intercompany transactions) within the MNE’s (OECD Transfer Pricing Guidelines, 2018). There is a lack of publicly available company financial data that may be used to calculate comparative benchmarks, and the information which is available, is not necessarily sufficient or adequate for comparability purposes (Tax Justice Network, 2013). Information which is accessible may be incomplete and difficult to interpret. In other cases information may be difficult to obtain for reasons of its geographical location and, in some instances, it may simply not be possible to obtain information from independent enterprises due to enterprise competitiveness and confidentiality concerns (OECD Transfer Pricing Guidelines, 2018). Despite all of these limiting factors, the arm’s length principle, as recommended by the OECD & UN Tax Model, remains the globally accepted guiding principle for calculating acceptable transfer prices. This is evident in the fact that almost all bilateral treaties in the world are based on these tax models (Steenkamp, 2017). For the last decade in South Africa, corporate tax has been the third largest contributor toward total revenue collection by National Treasury (National Treasury, 2017). It is therefore important that domestic tax laws should be able to protect the country’s tax base through legislation that discourages base erosion and profit shifting. The objective of this dissertation is to consider whether South Africa should continue to exclusively apply the arm’s length principle, which relies on comparable data, when determining transfer prices for goods in MNE’s. In testing this position, the following two alternative methods namely, formulary apportionment and predetermined margins, will be considered to evaluate whether or not these additional or complementary methods should be applied in the determination of arm’s length where comparable data is not available or requires significant adjustment as it relates to goods.